Cutaneous angiosarcoma: update on biology and latest treatment. Issue 2 (March 2018) - Ishida, Yoshihiro; Otsuka, Atsushi; Kabashima, Kenji
Abstract : Purpose of review: The present review aims to provide readers with the latest updates on the biology and clinical management of cutaneous angiosarcoma (cAS). Recent findings: The genomic alteration of cAS is heterogeneous. Mutations are enriched in the mitosis-activated kinase (MAPK) pathway. Functional analysis has identified molecules that may serve as potential markers and therapeutic targets of angiosarcoma. These molecules include survivin, HSP90, FOXM1, miR-497-5p, KCa3.1, and miR210. This body of knowledge has not yet transferred to clinical practice. The mainstay of treatment for cAS remains surgery followed by postoperative radiotherapy. The efficacy of paclitaxel as an adjuvant chemotherapy is suggested. For patients with advanced cAS, paclitaxel is the treatment of choice. There are also second-line treatment options that are supported by evidence of varying strength. A multikinase inhibitor, pazopanib, has been assessed in several studies, most of which support its efficacy for angiosarcoma. Bevacizumab monotherapy may be effective for angiosarcoma. The efficacy of eribulin mesylate and trabectedin for angiosarcoma is currently being assessed. Recent publications highlighted the role of the immune system in the biology of cAS. Summary: Future research efforts should focus on the following aspects of cAS: drug development directed at recent molecular targets, clinical trials designed specifically for patients with cAS, and the role of immunotherapy for cAS.